CANNIBALISM PERFORMANCE OF ASIAN REDTAIL CATFISH (Hemibagrus nemurus) FED RATION SUPPLEMENTED WITH DIFFERENT DOSES OF 17α-METHYLTESTOSTERONE - Heltonika, Benny; Sudrajat, Agus Oman; Junior, Muhammad Zairin; Widanarni, Widanarni; Suprayudi, Muhammad Agus; Manalu, Wasmen; Hadiroseyani, Yani (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2023)
One of the obstacles in Asian redtail catfish hatchery is the high cannibalism incidence. Cannibalism is associated with aggressive behavior caused by hormonal metabolism especially of testosterone. The purpose of this study was to evaluate the effect of testosterone administration on the cannibalism incidence in the Asian redtail catfish juveniles. The experiment was conducted by rearing fish with initial length of 4.09±0.19 cm in 16 of 20 L aquariums with a density of 2 fish L-1. The experiment was designed with a completely randomized design with 4 treatments which were different level of 17α-methyltestosterone supplementation in feed, i.e., 0 mg kg-1 feed (A) as control, 7.5 mg kg-1 feed (B), 15 mg kg-1 feed (C), and 30 mg kg-1 feed (D). Each treatment has 4 replications. Fish fed experimental diet (40% protein) 4 times a day to satiation for 30 days. The parameters observed were type and index of cannibalism, aggressive behavior, survival rate, normal mortality, growth performance, hormones concentrations (estradiol, testosterone, and cortisol), and water quality. The results showed that cannibalism type II (the fish eaten completely or missing) and cannibalism index increased with the increasing doses of testosterone administration in the feed with the highest cannibalism incidence was 40.63%. The highest survival rate was found in treatment B (73.75±2.50%) and was not significantly different from the control treatment (69.38±2.39%). No differences in testosterone concentration and in the growth performance among the treatments. However, there was a trend of decrease in the estradiol concentration of Asian redtail catfish juveniles fed ration supplemented with the increasing doses of 17α-methyltestosterone. Based on the results obtained in this research, estradiol changed in the body's plasma, it appears that there was a role for plasma estradiol concentration in controlling cannibalism of Asian redtail catfish juveniles. It concluded that the testosterone administration affected the cannibalism incidence in the Asian redtail Catfish.